Ekonomska analiza parničnog postupka / Economic Analysis of Civil Procedure - Omanović, Sanjin; Ruhotina, Anisa (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
The economic analysis of civil procedure has developed within the economic analysis of law as a broader scientific discipline, having as a subject studying the actions of the civil procedure, as well as the impact that norms of material and procedural laws have on their behavior. By using the findings of economic analysis of the civil procedure, the authors aim to answer the following questions: firstly, when the dispute should be solved in the litigation, i.e. when the requirements for settling of the dispute are met; secondly, in which way is it possible to reduce the total litigation costs and, finally, which impact the litigation costs have on the willingness of the parties to file a complaint in court.